Butrin Tackles Retinoblastoma – A Clinical Hypothesis † - Rakshana Manikandan; M. Mala; G. Manikandan; Prakash Vaithyanathan (International Journal of Advance in Molecular Engineering, 2024)
Breach of association of legumain protein activities to the corresponding cellular components results in over-expression of legumain, and constitutes a key biomarker for a variety of life-taxing sicknesses like cancer, Alzheimer’s/Parkinson’s and acute kidney injury. To suppress the functions of legumain, it is hypothesized that a water soluble and edible biomolecule, namely, butrin (7, 3’, 4’-trihydroxy flavanone-7, 3’-diglucoside) may have the therapeutic potential owing to its special ability to bind to the key catalytic sites of legumain, discovered through bioinformatic studies. Insights, into the docking structure of butrin were provided with emphasis on the relative binding abilities of various hydroxyl groups of butrin with the amino acid residues of the legumain protein.
Keywords: Acute kidney injury; Alzheimer’s disease; Biomarker; butrin; cancer tumor; legumain; molecular level interaction